2018
DOI: 10.1111/tbed.12915
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bovine Tuberculosis in India: A systematic review and meta-analysis

Abstract: Bovine tuberculosis (bTB) is a chronic disease of cattle that impacts productivity and represents a major public health threat. Despite the considerable economic costs and zoonotic risk consequences associated with the disease, accurate estimates of bTB prevalence are lacking in many countries, including India, where national control programmes are not yet implemented and the disease is considered endemic. To address this critical knowledge gap, we performed a systematic review of the literature and a meta‐ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 39 publications
0
60
1
Order By: Relevance
“…The genetic distance among the M. orygis identified in this study also supports this scenario, as the genomes of these isolates differ on average by 231 SNPs, suggesting independent infections in their countries of origin (Figure 3). Broader in-depth molecular analyses of cattle TB in South Asia, for which little data currently exist despite it representing a major public health threat (Rahim et al 2017, Srinivasan et al 2018) are needed to verify our hypothesis. Regarding M. orygis reported in animals other than cattle, our hypothesis would suggest that these likely represent spillovers from infected cattle, similar to the situation seen in M. bovis (Malone et al 2017).…”
Section: Resultsmentioning
confidence: 87%
“…The genetic distance among the M. orygis identified in this study also supports this scenario, as the genomes of these isolates differ on average by 231 SNPs, suggesting independent infections in their countries of origin (Figure 3). Broader in-depth molecular analyses of cattle TB in South Asia, for which little data currently exist despite it representing a major public health threat (Rahim et al 2017, Srinivasan et al 2018) are needed to verify our hypothesis. Regarding M. orygis reported in animals other than cattle, our hypothesis would suggest that these likely represent spillovers from infected cattle, similar to the situation seen in M. bovis (Malone et al 2017).…”
Section: Resultsmentioning
confidence: 87%
“…However, based on a random-effects meta-regression model analysis, Srinivasan et al [11], revealed a pooled prevalence estimate of 7.3% indicating that there may be an estimated 21.8 million infected cattle in India. [15].…”
Section: Discussionmentioning
confidence: 99%
“…There are chances of tuberculosis positive retired cattle being admitted to the gaushalas as tuberculosis is prevalent in both the organized and unorganized dairy sector in India, generating cows for the shelters [44,45]. Gaushala cows have been found to be often positive for tuberculosis, with higher prevalence rates than organized and rural farms [46,47]. India has the world's highest burden of human tuberculosis [48], and the possible role of gaushalas in the zoonotic transmission of this disease is a concern.…”
Section: Health Managementmentioning
confidence: 99%